Clinical Legal Education in the Legal Aid Institution Faculty of Law, Universitas Katolik Parahyangan - Ulfah, Maria (Pandecta Research Law Journal, 2017)
Pendidikan hukum klinis di Fakultas Hukum dapat dilaksanakan melalui kegiatan reguler di luar kurikulum. Beberapa kampus menerapkan metode CLE sebagai mata kuliah wajib dan ada yang diterapkan di mata kuliah penunjang. Fakultas Hukum, Universitas Katolik Parahyangan (UNPAR) Bandung mengembangkan CLE melalui kegiatan reguler yang diselenggarakan oleh Lembaga Bantuan Hukum Pengayoman--sebagai bentuk komitmen terhadap pengabdian masyarakat oleh para mahasiswa yang terlibat dalam program CLE. Artikel ini membahas tentang aktivitas kegiatan CLE yang dilakukan oleh LBH Pengayom yang diadopsi dari AS dan berkembang pesat di Asia termasuk Indonesia. Analisis juga terkait dengan keuntungan-keuntungan dan hambatan dalam penerapan CLE dalam kurikulum Fakultas Hukum.Clinical legal education in a Faculty of Law can be done through the curriculum or ongoing regular activities outside the curriculum. Many campuses have implemented clinical legal education in the compulsory courses or elective courses. Faculty of Law, Universitas Katolik Parahyangan (UNPAR) develop it through ongoing routine activities included in the â€œPengayomanâ€ Legal Aid Institution (LBH Pengayoman). Various activities in LBH Pengayoman intended to achieve community service in the field of law committed by the students and faculty for approximately. This paper intended to deliver an analysis of activities organized by Legal Aid Institution Pengayoman with clinical legal education that stems from the United States, known in Asia, and growing in Indonesia. The analysis also endeavour to identify a variety of benefits and barriers to clinical legal education through outside the curriculum of the Law Faculty.